Motivational Dynamics of Reward and Punishment in Shaping Students’ Learning Behavior - Melany, Melany; Simbolon, Dea Perselia; Husda, Azizah; Daulay, Irma Khoirot (Empiricism Journal, 2026)
Reward and punishment strategies are widely applied in EFL classrooms to manage student behaviour and enhance motivation, yet their combined motivational dynamics in the context of junior high schools remain underexplored. This study aims to investigate how systematically applied reward and punishment strategies affect students' intrinsic and extrinsic motivation, habitual behaviour, and learning interest. This study uses a Classroom Action Research design with a mixed approach. Qualitative data were collected through classroom observations and interviews with teachers, while quantitative data were obtained from 33 ninth-grade students using a validated questionnaire to measure students' motivation and learning behaviour. Content validity was confirmed by two expert validators. The results of the questionnaire analysis show that the provision of rewards has a positive impact on students' emotional conditions and learning motivation, with 84.8% of respondents reporting increased happiness and motivation after receiving rewards. In the context of punishment, 57.6% of students reported an improvement in behaviour. Additionally, it is indicated by classroom observations and teacher interviews that student engagement and confidence can be enhanced through direct verbal praise. On the other hand, student behaviour can be managed through the application of fair and constructive punishment, whereby reflection is encouraged rather than fear being instilled. The integration of proportional and education-based reward and punishment strategies has a positive impact on students' learning behaviour and motivation in the EFL classroom environment. These findings suggest that teachers should prioritise non-material rewards and restorative forms of punishment to encourage long-term intrinsic motivation and behavioural development.